2020
DOI: 10.3389/fenrg.2020.00149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CELF Pretreatment Severity on Lignin Structure and the Lignin-Based Polyurethane Properties

Abstract: The impact of pretreatment severity on the structure of CELF lignin and tensile properties of CELF lignin-based PU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…According to the E a , cross‐linking reactivities to the HDI could be related to both the molecular weight and the content of active hydroxyl groups per mass unit, with an order of HDAAL L > DAAL L > AAL (Table 6). According to the literature and the results of the study, it was confirmed that the reactivity of the lignin substitute in the synthesis of LPUE was closely related to the molecular weight and structure features 44,45 . Lignin with high molecular weight usually had a complex molecular structure and strong intermolecular hydrogen bonding, which seriously limited the lignin dispersion in the LPUE.…”
Section: Resultsmentioning
confidence: 59%
“…According to the E a , cross‐linking reactivities to the HDI could be related to both the molecular weight and the content of active hydroxyl groups per mass unit, with an order of HDAAL L > DAAL L > AAL (Table 6). According to the literature and the results of the study, it was confirmed that the reactivity of the lignin substitute in the synthesis of LPUE was closely related to the molecular weight and structure features 44,45 . Lignin with high molecular weight usually had a complex molecular structure and strong intermolecular hydrogen bonding, which seriously limited the lignin dispersion in the LPUE.…”
Section: Resultsmentioning
confidence: 59%
“…The preparation of CELF lignin was described in a previous study . In brief, the milled poplar biomass (7.5 wt % solids loading) was treated in THF/water (1:1 w/w) solution containing 0.5 wt % sulfuric acid in a 1 L Hastelloy Parr autoclave reactor (Parr Instruments Co., Moline, IL).…”
Section: Methodsmentioning
confidence: 99%
“…The polycondensation reaction between polyols and PMDI was catalyzed by 1.5% DTDL in THF . The CELF lignin samples (MCL, LCL, and CL180) and the selected hydroxyl providers such as c BED, BD, OD, PEG400, and PEG4k were employed for fabricating CL-PUs according to the formulations listed in Table .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent progress in developing fractionation processes included finding novel and better solvent systems, such as organic co‐solvent systems using γ‐valerolactone (GVL) [24] and tetrahydrofuran (THF), [25] ionic liquid (IL), [26–29] and deep eutectic solvent (DES) systems [30,31] . Although these systems are effective in efficiently solubilizing lignin and/or hemicelluloses to obtain highly digestible cellulosic fraction for enzymatic sugar production, the resultant lignin from most of these solvent systems was condensed except when fractionation was conducted under mild conditions, which decreased the enzymatic digestibility of the fractionated solids [21,32–35] . Moreover, the significantly higher costs of GVL, IL, and THF compared with conventional alkali and mineral acids, along with the higher dosages (concentrations) needed for these solvents to be effective, require a very high chemical recovery efficiency that is too difficult to achieve for economical biorefinery operations.…”
Section: Introductionmentioning
confidence: 99%